Buying Local or Imported Goods? Profiling Non-income Consumers in Developing Countries - Ayob, Abu H; Wan Hussain, Wan Mohd Hirwani (International Review of Management and Marketing, 2016)
This study attempts to profile non-income consumers by examining their decisions to buy local or imported products. Hypotheses were drawn from discussions on the comparative advantages of advanced and developing countries, as well as the effects of a product's country-of-origin on customers' purchasing decisions. Data was collected on 296 university students in Malaysia and analysed through probit regression analysis. The findings reveal that foreign products from advanced countries are preferred by male students because of the superior quality and brand image. On the other hand, family members encourage students to buy local products because they are perceived as being less expensive. Also, students who receive scholarships are more likely to buy local products than self-sponsored students. This research offers insights into ex-ante purchasing behaviour in developing countries particularly among non-income consumers. Keywords: local products, imported products JEL Classifications: F1, F4, Q37